The Combined Effects of Irrigation, Tillage and N Management on Wheat Grain Yield and Quality in a Drought-Prone Region of China - Ming Huang; Ninglu Xu; Kainan Zhao; Xiuli Huang; Kaiming Ren; Yulin Jia; Shanwei Wu; Chunxia Li; Hezheng Wang; Guozhan Fu; Youjun Li; Jinzhi Wu; et al. (Agronomy)
With the swift progression of the High-Standard Farmland Construction Program in China and worldwide, many dryland wheat fields can be irrigated once during the wheat growth stage (one-off irrigation). However, the combined strategies of one-off irrigation, tillage, and N management for augmenting wheat grain yield and quality are still undeveloped in drought regions. Two-site split–split field experiments were conducted to study the impacts of irrigation, tillage, and N management and their combined effects on grain yield; the contents of protein and protein components; processing quality; and the characteristics of N accumulation and translocation in wheat from a typical dryland wheat production area in China from 2020 to 2022. The irrigation practices (I0, zero irrigation and I1, one-off irrigation), tillage methods (RT, rotary tillage; PT, plowing; and SS, subsoiling) and N management (N0, N120, N180, and N240) were applied to the main plots, subplots and sub-subplots, respectively. The experimental sites, experimental years, irrigation practices, tillage methods, and N management methods and their interaction significantly affected the yield, quality, and plant N characteristics of wheat in most cases. Compared to zero irrigation, one-off irrigation significantly increased the plant N accumulation, enhancing grain yield by 33.7% while decreasing the contents of total protein, albumin, globulin, gliadin, and glutenin by 4.4%, 6.4%, 8.0%, 12.2%, and 10.0%, respectively. It also decreased the wet gluten content, stability time, sedimentation value, extensibility by 4.1%, 10.7%, 9.7%, and 5.5%, respectively, averaged across sites and years. Subsoiling simultaneously enhanced the aforementioned indicators compared to rotary tillage and plowing in most sites and years. With the increase in N rates, wheat yield firstly increased and then decreased under zero irrigation combined with rotary tillage, while it gradually increased when one-off irrigation was combined with subsoiling; however, the contents of total protein and protein components and the quality tended to increase firstly and then stabilize regardless of irrigation practices and tillage methods. The correlations of yield and quality indicators with plant N characteristics were negative when using distinct irrigation practices and tillage methods, while they were positive under varying N management. The decrease in wheat quality induced by one-off irrigation could be alleviated by optimizing N management. I1STN180 exhibited higher yield, plant N accumulation and translocation, and better quality in most cases; thus, all metrics of wheat quality were significantly increased, with a yield enhancement of 50.3% compared to I0RTN180. Therefore, one-off irrigation with subsoiling and an N rate of 180 kg ha−1 is an optimal strategy for high yield, high protein, and high quality in dryland wheat production systems where one-off irrigation is assured.